Pengaruh Kebisingan Terhadap Performansi Sistem Refrigerasi - Sugina, I Made (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
Noise is a longitudinal wave which is known as pressure wave. Therefore, noise is expected to disturb the stability of fluid flow. The disturbance is expected to increase the heat transfer of fluid flow. In this research, noise was applied to condenser cooling of air in a refrigeration system. Effect generated is directly measured by amount of heat capable to be released into the air passing condenser, and indirectly by the compressor energy required and coefficient of performance (COP) of refrigeration system. Experimental results indicate that noise with intensity level of 115 dB with frequency around 100–500 Hz at air velocity of 5,3 m / s increases the amount of heat capable to be released into the air which is 10,1%, reduces compressor energy to 12,8% and increases coefficient of performance (COP) by 11,4% compared to flow without noise.